Regulasi Emosi pada Korban Bullying di SMP Batik Surakarta - Aufi Rahma Fahrunisa (Prophetic guidance and counseling journal, 2022)
This study aims to find out about how the form of emotional regulation shown in victims of bullying and the causes that can be accepted in victims of bullying to not respond to bullying. This research is a qualitative research with descriptive approach. Data collection techniques using observation, interviews and documentation. The subjects involved in this study amounted to seven students of 7, 8 and 9 grade of SMP Batik Surakarta. The results are in accordance with the aspects of emotional regulation that cause victims to adjust to the bullying experienced, among others: (1) the ability to monitor emotions, namely the belief of individuals to understand the whole process that occurs in a problem, such as realizing the bullying actions that victims get and choose to respond calmly, (2) the ability to evaluate emotions, namely the ability of individuals to manage emotions experienced, such as choosing to play with other friends as a diversion of emotions felt, (3) the ability to modify emotions is the ability of individuals to change emotions into self-motivation, the victim has the motivation to focus on studies that are being pursued and improve academic achievement to be able to make the victim's parents happy. Based on the results of the study concluded that the high level of emotional regulation possessed by the victim makes the victim does not respond to the actions of the perpetrator, so that the victim is quite able to limit the impact of bullying so as not to reach too far into the victim's life and assume that the act of bullying experienced is only temporary. The form of attitude that is carried out on the victim of bullying so as not to retaliate for the bullying committed by the perpetrator is the existence of supporting factors such as victim awareness to focus on school in order to get satisfactory grades and graduate well, as well as the belief in the victim that the characteristics and properties of different people. Bullying victims get bullying actions also caused by low interpersonal skills. The victim's inability to interact causes the victim to be less able to blend in with the school environment so that the victim is considered a quiet individual and becomes an easy target for bullies. Abstrak Penelitian ini bertujuan untuk mengetahui tentang bagaimana bentuk regulasi emosi yang ditunjukkan pada korban bullying serta penyebab yang dapat diterima pada korban bullying hingga tidak membalas tindakan bullying. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Teknik pengambilan data menggunakan observasi, wawancara serta dokumentasi. Subjek yang terlibat dalam penelitian ini berjumlah tujuh orang siswa-siswi kelas 7, 8 dan 9 SMP Batik Surakarta. Adapun hasil yang sesuai dengan aspek regulasi emosi yang menyebabkan korban dapat menyesuaikan diri terhadap bullying yang dialaminya antara lain: (1) Kemampuan memonitor emosi yaitu keyakinan individu untuk memahami keseluruhan proses yang terjadi pada suatu masalah, seperti menyadari tindakan bullying yang korban dapatkan serta memilih untuk menyikapi dengan tenang, (2) Kemampuan mengevaluasi emosi yaitu kemampuan individu untuk mengelola emosi yang dialami, seperti memilih bermain dengan teman lain sebagai pengalihan emosi yang dirasakan, (3) Kemampuan memodifikasi emosi yaitu kemampuan individu untuk merubah emosi menjadi motivasi diri, korban memiliki motivasi untuk memfokuskan diri pada studi yang sedang ditempuh dan meningkatkan prestasi akademik untuk dapat membahagiakan orang tua korban. Berdasarkan hasil penelitian disimpulkan bahwa tingginya tingkat regulasi emosi yang dimiliki oleh korban membuat korban tidak membalas tindakan pelaku, sehingga korban cukup mampu membatasi dampak bullying agar tidak terlalu jauh menjangkau kehidupan korban dan menganggap bahwa tindakan bullying yang dialami hanya sementara. Bentuk sikap yang dilakukan pada korban bullying sehingga tidak membalas perbuatan bullying yang dilakukan pelaku yaitu adanya faktor pendukung seperti kesadaran korban untuk fokus pada sekolah agar mendapatkan nilai yang memuaskan dan lulus dengan baik, juga keyakinan dalam diri korban bahwasanya karakteristik dan sifat orang yang berbeda-beda. Korban bullying mendapatkan tindakan bullying juga disebabkan karena rendahnya kemampuan interpersonal yang dimiliki. Ketidakmampuan korban untuk berinteraksi menyebabkan korban kurang mampu untuk membaur dengan lingkungan sekolah sehingga korban dianggap sebagai individu yang pendiam dan menjadi target yang mudah bagi para pelaku bullying.